Glioblastoma in elderly patients: solid conclusions built on shifting sand? - Wick, Antje; Keßler, Tobias; Winkler, Frank; Platten, Michael; Wick, Wolfgang (Neuro-Oncology, 2018)
Management of glioblastoma in the elderly population is challenging. In the near future, more than half of patients with this tumor will be over the age of 65. Clinicians have been historically reluctant to treat such patients with the same intensity as younger patients. Due to upper age limits or poor accrual of elderly patients in clinical trials, randomized data for this patient population have been relatively sparse until recently. In this review, we will discuss the concept of an elderly patient population, describe evidence for molecular differences in glioblastoma of elderly versus young patients, evaluate recent first-line trials studying glioblastoma in elderly patients, and discuss best therapeutic practices including the value of molecular testing.
Published: 18 July 2017
Gesehen am 12.03.2020